2015
DOI: 10.3892/ijmm.2015.2182
|View full text |Cite
|
Sign up to set email alerts
|

Melia azedarach extract stimulates melanogenesis through increase of tyrosinase-related protein 1 expression in B16F10 mouse melanoma cells

Abstract: Abstract. Melia azedarach (MA) has been used in folk medicine in Asia for the treatment of several diseases. Several constituents from MA possess anti-herpetic, anti-angiogenic and anticancer properties. The aim of the present study was to investigate the effect of a 70% ethanol extract of MA on melanogenesis and the underlying mechanisms involved. A B16F10 mouse melanoma cell line was used in our experiments. Treatment of B16F10 cells with the MA extract (10, 20 and 40 µg/ml) increased melanin content in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Briefly, we found increase in the expression of cAMP, MITF, and TRP1 but not tyrosinase expression after cellular incubation with ED (4a and 6b) and PAED (4a and 6b). A recent report 49 represents similar results in which Melia azedarach (MA) extract increased the melanin content in B16F10 cells without affecting intracellular tyrosinase. Conversely, the Melia azedarach (MA) extract remarkably increased the expression of TRP1 protein.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Briefly, we found increase in the expression of cAMP, MITF, and TRP1 but not tyrosinase expression after cellular incubation with ED (4a and 6b) and PAED (4a and 6b). A recent report 49 represents similar results in which Melia azedarach (MA) extract increased the melanin content in B16F10 cells without affecting intracellular tyrosinase. Conversely, the Melia azedarach (MA) extract remarkably increased the expression of TRP1 protein.…”
Section: Discussionsupporting
confidence: 58%
“…Conversely, the Melia azedarach (MA) extract remarkably increased the expression of TRP1 protein. Therefore, they concluded that TRP1 is responsible for higher melanin production 49 . Interestingly, in another study the down-regulation of TRP1 was reported to be involved in melanin inhibition but there was no significant change in the expression of tyrosinase 50 .…”
Section: Discussionmentioning
confidence: 99%
“…70% ethanol extract of Melia azedarach was demonstrated to rapidly increase melanin content in a concentration-dependent manner within 4 h [ 50 ]. Additionally, although the extract did not affect intracellular tyrosinase activity, protein levels of tyrosinase and TRP-2 at 2 and 4 h after treatment, it could improve TRP-1 protein expression at both time points.…”
Section: Melanogenesis Stimulators From Different Sourcesmentioning
confidence: 99%
“…The fact that CK stimulated melanogenesis led us to the hypothesis that CK does not have a whitening effect but might possess photoprotection activity at the cellular level. This UVB-protective effect suggests that CK can retard skin damage such as skin aging and wrinkle formation [5] , [43] . It is possible that some biological activities of CK could be managed by melanin action [42] .…”
Section: Resultsmentioning
confidence: 96%
“…2 C), implying that CK could not modulate melanin synthesis process as well as secretion pathway. Melanogenesis is a complex biological process to synthesize melanin, which protects the skin from UV irradiation [42] , [43] . CK did not have any influence on tyrosinase activity or extracellular melanin secretion, but did increase intracellular melanin levels.…”
Section: Resultsmentioning
confidence: 99%